Political and Economic Relation in The SAARC Countries (Researcher CAB: A Journal for Research and Development, 2023)
The level of cooperation among the member countries of SAARC has increased after its formation in 1985. SAARC was founded with the objective to improve living standards of the people, contribute to political, cultural and regional economic growth and to increase cooperation with another region of the world. Realizing the importance of regional cooperation and development, SAARC members have cooperated to establish and initiate various programs and forums for mutual benefit. Agreement on Judicial cooperation on Counter-Terrorism, establishment of Development Funds, Telemedicine Network, SAARC Writers and Literature Foundation, South Asia Women’s Centre and South Asia Olympic Council. Other major achievements include adoption of Social Charter in 2004, establishment of SAARC Arbitration Council in Islamabad in 2005, and establishment of SAARC Energy Center in Islamabad (2006), South Asian Regional Standards Organization (SARSO) was established in Dhaka (2014), SAARC Disaster Management Center was established in Gujarat in Nov 2016. Area of cooperation has been extended from five to eight. The economic ties and integration have not been very strong in SAARC countries.